Mother Figure in Indonesian Children Book Illustration in Terms of Attribute, Domestic, and Public Space - Sihombing, Riama Maslan (ASPENSI in Bandung, Indonesia, 2012)
ABSTRACT: A mother is often viewed as someone who is full of love, tender, helpful, nurtured, and loving her children unconditionally. Illustrators picture a mother in a certain worldview, so that cultural constellation can be seen in the illustration of a mother in children books. This paper aims to investigate the identity of a mother in children bookâs illustration pictured in personal and public space by descriptively reviewing meanings and codes of a mother on illustration using semiotic theory. This research, then, took ten children book illustration published in the 1980s â 1990s with ten purposive samples and some samples taken from year 2000 as comparison. This research is a preliminary study to find meaning of a mother figure illustrations with the finding that the traditional stereotype of the mother appears with a distinctive attribute of mothers wearing a âkebayaâ, a hair bun and present in domestic sphere; and in further development, a mother appears in public space as a consequence to the change of her position as the breadwinner of the family. KEY WORDS: Mother figure, children bookâs illustration, stereotype, Indonesian family, and social changes.About the Author: Riama Maslan Sihombing is a Ph.D. Candidate and as a Lecturer at Faculty of Art and Design ITB (Bandung Institute of Technology), Jalan Ganesha No.10 Tamansari, Bandung, West Java, Indonesia. She can be reached at: riamamaslansihombing@gmail.comHow to cite this article? Sihombing, Riama Maslan. (2012). âMother Figure in Indonesian Children Book Illustration in Terms of Attribute, Domestic, and Public Spaceâ in TAWARIKH: International Journal for Historical Studies, Vol.3(2) April, pp.253-264. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (February 2, 2012); Revised (March 4, 2012); and Published (April 28, 2012).